Cell-specific CRISPR-Cas9 activation by microRNA-dependent expression of anti-CRISPR proteins - Hoffmann, Mareike; Aschenbrenner, Sabine; Große, Stefanie; Rapti, Kleopatra; Domenger, Claire; Fakhiri, Julia; Mastel, Manuel; Börner, Kathleen; Eils, Roland; Grimm, Dirk; Niopek, Dominik (Nucleic acids research, 2019)
Abstract. The rapid development of CRISPR-Cas technologies brought a personalized and targeted treatment of genetic disorders into closer reach. To render CRIS
Gesehen am 03.01.2020